Seleksi Genotipe Padi Mutan Insersi Toleran Cekaman Salinitas Berdasarkan Karakter Pertumbuhan dan Biokimia - Apriadi Situmorang; Anky Zannati; Dwi Widyajayantie; Satya Nugroho (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Eleven genotypes of insertional mutant Nipponbare rice carrying randomly inserted activation tag were tested to investigate the growth and biochemical responses to salt stress. Pokkali, IR 29, and non-transgenic Nipponbare were used as tolerant, susceptible, and isogenic control, respectively. Plants were grown in plastic trays filled with 0 g L-1 NaCl Yoshida nutrient solution as control and grown in 6 g L-1 NaCl as treatment. Salt injury was scored on 10, 16, and 21 days after salinization. Observation at 21 days after salinization showed that there was significant difference among genotypes in growth and biochemical characters. Classification using hierarchical cluster analysis based on growth and biochemical responses showed that there were three clusters. Cluster I consisted of wild-type Nipponbare, T2.pMO.V.3.13.c.22, T2.pMO. V.1.7.a.15, T2.pMO.III.98.b.7, T2.pMO.II.231.c15, T2.pMO.III.98.b.8, T2.pMO.III.98.b.17, T2.pMO.III.98.b.3, and T2.pMO.VI.81.3.a.4. Cluster II consisted of IR 29, T2.pMO.V.3.13.c.14, T2.pMO.VI.30.1a.125, and T2.pMO.VI.30.1.a.65. However no mutant genotype was clustered with Pokkali in cluster III, which may indicate that there was no salt tolerant mutant genotype found in this research. Keywords: salt tolerance mutant rice, growth characters, biochemical characters